Longer is not necessarily better: Career paths of academic entrepreneurs and university spin-off growth in Germany - Nora Hesse (European Regional Science Association (ERSA), 2013)
Universities are increasingly seen as engines for regional innovation and economic growth. Some famous high-tech regions have developed on the basis of universities, for example Silicon Valley in California, Greater Boston in Massachusetts, or the Research Triangle in North Carolina. In these regions, university spin-offs are regarded as one important vehicle of knowledge transfer and commercialization from university to industry. In this paper the focus is on the persons who are behind these processes. Academic entrepreneurs develop great ideas at university and decide to put them into practice. One famous example is the Stanford University PhD Student Larry Page, who founded the internet search engine Google. Academic entrepreneurs are persons of different university career levels, from students over research staff to professors. The aim of this paper is to investigate how the academic entrepreneurs? university career level can affect university spin-off growth in terms of job creation. Therefore, research questions are derived from three theoretical perspectives: human capital, university status and role identity. My empirical analysis is based on qualitative survey data from two German midrange universities. I carried out a total of 85 semi structured face-to-face and telephone interviews with academic entrepreneurs during the period September 2011 to January 2012. The analytical process relied on a qualitative content analysis and extreme case analysis. I show that, in order to distinguish high growth from low growth university spin-offs, it is important to understand the interactions of the academic entrepreneur?s human capital, university status and role identity. By investigating the academic entrepreneurs? career paths in-depth, it becomes clear that every university career level comprises certain advantages to benefit from and disadvantages to cope with. These findings contribute to a better understanding of the factors which influence university spin-off growth and can help to improve university spin-off support. This paper is structured as followed: First of all the three theoretical perspectives are discussed and three research questions are derived (section 2). After introducing the data and methods used in this paper and pointing out limitations (section 3), empirical results of the qualitative content analysis (section 4) and extreme case analysis (section 5) are discussed. Finally, a conclusion is drawn (section 6).
Keywords: L26; M13; J23; 330; Academic Entrepreneurship; Job Creation; University Spin-offs; University; Career Paths